Application of immobilized сells on mineral sorbents in areid condition of atyrau region (Eurasian Journal of Ecology, 2016)
The article contains information on the use hydrocarbon-oxidizing activity of free and immobilized cells of microorganisms- oil oxidizing mineral sorbents in the arid conditions at the field «Koschagyl» Atyrau region.
Keywords: oil; soil; sorbent; immobilization of cells; hydrocarbon-oxidizing microorganisms